Analysis of velocity and pressure vector distribution fields in a three-dimensional plane around a wind power plant - Bakhtybekova, A.R.; Tanasheva, N.K.; Shuyushbayeva, N.N.; Minkov, L.L.; Botpaev, N.K. (Karagandy University of the name of acad. E.A. Buketov, 2022)
To date, there has been an increase in demand for electric energy obtained from clean renewable energy sources. One of them is wind power. Based on this, the development and research of new types of efficient wind turbines that start working at low wind speeds is an urgent issue. Wind turbines operating based on the Magnus effect have proven their effectiveness. However, the authors of this work, for the first time, to eliminate the problem in the form of an electric drive for the promotion of cylindrical blades added a deflector element to the end of the cylinders. Before creating an experimental setup, it is necessary to numerically investigate the aerodynamics around the wind wheel. For this purpose, numerical simulation of wind wheel aerodynamics has been carried out using the highly efficient Ansys Fluent program. A three-dimensional geometry has been created in Design Modeler. A mathematical model grid with a grid number of 47329 consisting of tetragonal cells is constructed. The Realizable k-ε is chosen as the turbulence model. A thorough analysis of the velocity vector distribution fields for flow and pressure velocities in the three-dimensional plane around the wind wheel at air flow velocities of 5.10 and 15 m/s is carried out.
Жел энергетикалық қондырғысының айналасындағы үш өлшемді жазықтықтағы жылдамдық пен қысым векторларының таралу өрістерін талдау
Анализ полей распределения векторов скоростей и давления в трехмерной плоскости вокруг ветроэнергетической установки
Keywords: wind power plant; Ansys Fluent; Magnus effect; deflector; mathematical model; numerical simulation